Increasing students' Understanding in Medical Surgical Nursing courses about Factors That Can Affect Early Mobilization of Mothers Post Sectio Caesarea at the Rumah Sakit Ibu dan Anak Banda Aceh - Yeni Rimadeni, (Jurnal Serambi Ilmu, 2024)
The purpose of this study was to determine and improve the ability of students directly about the factors that influence the early mobilization of postoperative cesarean mothers. This study uses a descriptive correlational research method with the approach used is cross sectional. The number of samples of 30 respondents was taken using the Non Probability sampling method with accidental sampling technique. The results showed that there was no relationship between pain and early mobilization with a P-value (0.784), there was no relationship between anxiety levels and early mobilization with a P-value (0.445), there was a relationship between knowledge and early mobilization with a P-value (0.008). and there is a relationship between motivation and early mobilization with a P-value (0.001). Factors that influence early mobilization of postoperative sectio caesarea mothers at the Rumah Sakit Ibu dan Anak Banda Aceh are influenced by several factors such as knowledge and motivation. From the results of this study, it is hoped that it can be useful for postoperative sectio caesarea mothers, for hospitals to be able to improve the evaluation of early mobilization in postoperative sectio caesarea mothers from pain factors, anxiety levels, knowledge and motivation